2012
DOI: 10.1111/j.1468-2419.2011.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Team creativity: the effects of perceived learning culture, developmental feedback and team cohesion

Abstract: This study investigates the influence of perceived learning culture, developmental feedback and team cohesion on team creativity. The results showed that the demographic variables, the three antecedents and their interactions explained 41 per cent of variance in team creativity. Team creativity was positively correlated with a higher level of learning culture, developmental feedback and team cohesion. In addition to the main effects, two interaction effects (developmental feedback and team cohesion; learning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 68 publications
(90 reference statements)
2
62
0
1
Order By: Relevance
“…Our aim in this study was to examine how developmental feedback affects employee job performance. Prior researchers have confirmed that supervisor developmental feedback is positively associated with positive employee work attitudes and behavior (Joo, Song, Lim, & Yoon, 2012;Li, Harris, Boswell, & Xie, 2011;Yin & Zheng, 2011). However, few researchers have examined an intermediate process through which developmental feedback influences employee work behavior.…”
mentioning
confidence: 87%
“…Our aim in this study was to examine how developmental feedback affects employee job performance. Prior researchers have confirmed that supervisor developmental feedback is positively associated with positive employee work attitudes and behavior (Joo, Song, Lim, & Yoon, 2012;Li, Harris, Boswell, & Xie, 2011;Yin & Zheng, 2011). However, few researchers have examined an intermediate process through which developmental feedback influences employee work behavior.…”
mentioning
confidence: 87%
“…Self-expectations that creative professionals ought to have more confidence in creative endeavors than professionals in non-creative industries are realized. 0.12*** 0.25*** 0.16*** Note *p < 0.05, **p < 0.01, ***p < 0.001 (female = 0; male = 1) Also, professionals in creative and super-creative industries incline to work with sophisticated skills at creating new knowledge and insight in an organizational culture that can encourage innovative practices, and thus creativity of these professionals (Joo et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Group atmosphere Group atmosphere refers to "psychological conditions prevailing in an organization" or a group and is at times used synonymously with "organizational climate" (Ekvall & Ryhammar, 1999). It seems that a positive group atmosphere is invariably beneficial for a group to achieve a high level of creativity in the case of both adults in a professional organization setting (Ekvall & Ryhammar, 1999;Joo et al, 2012;Schepers & Berg, 2007) and children in a classroom situation (Dudek, Strobel, & Rundo, 1993;Fleith et al, 2002;Hu et al, 2013). This may be because the group atmosphere or classroom climate setting implicitly suggests "basic values" that the members of a group should follow (Ekvall & Ryhammar, 1999).…”
Section: Group Diversitymentioning
confidence: 99%